Is There a Debt-Threshold Effect on Output Growth? - Chudik, Alexander; Mohaddes, Kamiar; Pesaran, M. Hashem; Raissi, Mehdi (The Review of Economics and Statistics, 2017)
This paper studies the relationship between public debt expansion and economic growth and investigates whether the debt-growth relation varies with the level of indebtedness. We contribute theoretically by developing tests for threshold effects in the context of dynamic heterogeneous panel data models with cross-sectionally dependent errors. In the empirical application, using data on a sample of forty countries over the 1965–2010 period, we find no evidence for a universally applicable threshold effect in the relationship between public debt and economic growth. Regardless of the threshold, however, we find significant negative effects of public debt buildup on output growth.